Diagnosis and treatment principle in Sasang medicine: original symptom - Seungwon Shin; Yun-Hee Kim; Min-Woo Hwang (Integrative Medicine Research)
The purpose of this review was to demonstrate the definition of the original symptom (OS) and how it works in medical procedures as to the Sasang medicine based on the Jema Lee's Donguisusebowon (Longevity and Life Preservation in Eastern Medicine). OS is defined as the sum of all clinical information featured by an individual's intrinsic characteristics as Sasangin and health state prior to onset. It is the key factor in the clinical application of Sasang medicine including the diagnosis of constitutional type and Sasang symptomatology because the imbalance of metabolic functions of each Sasangin originates from that. The working principles of the OS and Sasang symptomatology can be summarized as follows. First, clinical information regarding cold or heat intolerance determines the cold or heat pattern of Sasang symptomatology. Another is the present worsening of the severity of Sasang symptomatology by one level as compared with that in the past. Symptoms prior to the onset worsen to a higher level of severity after any disorder breaks out. Finally, the treatment strategy and progress of each Sasangin are determined following the characteristics of the OS. Theoretical and clinical studies should be conducted to show the specific criteria for the diagnosis of Sasang symptomatology in the future.